From scrappy to self-made : what entrepreneurs can learn from an Ethiopian refugee to turn roadblocks into an empire - Hagos, Yonas (McGraw Hill-Ascent Audio, 2023)
Former Ethiopian refugee Yonas Hagos shares his amazing story about his plight in Ethiopia, his emigration to the US, and the business journey he took to become the owner of dozens of restaurant franchises. From Scrappy to Self-Made describes how Hagos beat all the odds to become the owner of more than four dozen restaurant franchises that have earned him $10 million, and counting. He owns and operates more than fifty restaurants, including Arby's, Nothing Bundt Cakes, and multiple outlets of Smoothie King, Dunkin' Donuts-and coming soon, Kaia Tapas and Beach Life. A tale of entrepreneurship focusing on the roadblocks aspirational business owners most commonly encounter, this how-to, self-help guide provides personal stories and feet-on-the-street advice. Hagos covers his assimilation into a different culture while delving into every single aspect of what it takes to launch a successful business, to fail at running one, to learn from mistakes, and to move on to sustained success. Melding the how-to, self-help business book with gripping personal stories, From Scrappy to Self-Made is a tale of entrepreneurship that focuses on the roadblocks aspirational business owners encounter.